NADPH oxidase 5 is a novel susceptibility gene for type 2 diabetes mellitus - Azarova, Iuliia; Klyosova, Elena; Azarova, Valentina; Polonikov, Alexey (Archives of Endocrinology and Metabolism, 2024)
This pilot study investigated whether single nucleotide polymorphisms (SNP) in the NOX5 gene (NADPH oxidase 5) are associated with the type 2 diabetes (T2D) risk. A total of 1579 patients with T2D and 1627 age- and sex-matched healthy subjects were recruited for this study. Genotyping of common SNPs, namely rs35672233, rs3743093, rs2036343, rs311886, and rs438866, was performed using the MassArray-4 system. SNP rs35672233 was associated with an increased risk of T2D (OR = 1.67, 95% CI 1.29-2.17, FDR = 0.003). The H3 haplotype (rs35672233T-rs3743093G-rs2036343A-rs311886C-rs438866C) increased T2D risk (OR = 1.65, 95% CI 1.27-2.13, FDR = 0.001). The rs35672233 polymorphism and H3 haplotype were found to have an association with T2D risk only in subjects with a body mass index greater than 25 kg/m (FDR < 0.01). Environmental risk factors, such as chronic psycho-emotional stress, sedentary lifestyle, high-calorie diet and SNP rs35672233 were jointly associated with T2D susceptibility. A haplotype comprising the allele rs35672233-C and conferring protection against T2D, was associated with elevated levels of antioxidants such as total glutathione and uric acid, as well as reduced levels of two-hour postprandial glucose in the plasma of patients. The NOX5 polymorphisms showed no associations with diabetic complications. The present study is the first to establish associations between polymorphisms in NOX5 and the risk of type 2 diabetes mellitus, and provides a new line of evidence for the crucial role of oxidative stress-related genes in disease susceptibility.